2016
DOI: 10.3906/sag-1501-124
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in androgen metabolism genes AR, CYP1B1, CYP19, and SRD5A2and prostate cancer risk and aggressiveness in Bulgarian patients

Abstract: Background/aim: The aim of our study was to elucidate the role of polymorphisms in AR, CYP1B1, CYP19, and SRD5A2 genes for prostate cancer (PC) development in Bulgarian patients. Materials and methods:We genotyped 246 PC patients and 261 controls (155 with benign prostate hyperplasia and 107 healthy population controls) using direct sequencing, PCR-RFLP, SSCP, and fragment analysis. Results:The allele and genotype frequencies of most of the studied variants did not differ significantly between cases and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Recently microarray data from the livers of the CYP1B1 KO mice that are resistant to diet-induced obesity indicated that CYP1B1 deletion substantially alters the expression of genes associated with fatty acid homeostasis [33]. Several studies have examined the relationship between individual CYP1B1 polymorphisms and cancer risk [14,15,[34][35][36][37]. However, very limited data are available for CYP1B1*2 (rs1056827G>T) genetic variants in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Recently microarray data from the livers of the CYP1B1 KO mice that are resistant to diet-induced obesity indicated that CYP1B1 deletion substantially alters the expression of genes associated with fatty acid homeostasis [33]. Several studies have examined the relationship between individual CYP1B1 polymorphisms and cancer risk [14,15,[34][35][36][37]. However, very limited data are available for CYP1B1*2 (rs1056827G>T) genetic variants in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion and exclusion criteria, a total of 14 studies [14,[16][17][18][19][24][25][26][27][28][29][30][31][32] were deemed eligible for this meta-analysis ( Figure 1 detailed the study selection process). Among them, 8 studies investigated only the Arg264Cys polymorphism [14, 16-18, 24-26, 28], 5 studies explored only the (TTTA)n repeat polymorphism [19,[29][30][31][32], and 1 study focused on both polymorphisms [27]. The main characteristics of these studies are listed in Supplementary Table 1 (see Additional le 1) and…”
Section: Selection and Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…This SNP is a C > T transition in exon 7 of CYP19A1 gene and results in the substitution of Arg at position 264 by Cys. No association was reported among Bulgarians [94], African Americans [95], and Japanese [96]. However, a study on North Indian population showed that the variant Cys was associated with statistically significant increased risk of prostate cancer (OR = 2.28; 95% CI = 1.20-4.35; p = 0.012) [97].…”
Section: Variations In Cyp19a1 Gene and Prostate Cancermentioning
confidence: 99%
“…The coexisting ins allele and (TTTA)12 also in the CYP19A1 reduced the risk of developing prostate cancer. More recently, Kachakova et al [94] have shown that the 7/8 genotype of (TTTA)n repeat polymorphism in CYP19A1, when coexisting with the C allele of rs1056837 in CYP1B1, predisposes to prostate cancer, while the 8/9 and the 7/12 genotypes of (TTTA)n of CYP19A1 when existing with the C allele of CYP1B1 associate with lower risk of prostate cancer and a reduced risk for aggressive disease.…”
Section: Variations In Cyp19a1 Gene and Prostate Cancermentioning
confidence: 99%